Praktik Multigrade Teaching dalam Pendidikan Nonformal Hindu: Studi Kualitatif Pada Pasraman di Lombok Barat - Ida Bagus Kade Yoga Pramana; I Wayan Rudiarta; Ni Wayan Ria Lestari; Ni Nengah Sudarsini (Jayapangus Press, 2026)
Multigrade teaching in the context of Hindu non-formal education in pasraman poses its own pedagogical challenges for acaryas, especially in managing students with diverse age levels and abilities in a single class. Studies on multigrade learning practices in Hindu religious education institutions are still relatively limited, especially in the context of pasraman in the West Lombok region. Therefore, this study aims to examine and analyse the multigrade learning practices applied by acaryas in pasramans in West Lombok Regency. This study uses a qualitative, narrative-descriptive approach to examine multigrade learning in pasraman in depth. Research data were collected through observation, interviews, and documentation. The collected data is analysed through the stages of data reduction, data presentation, data verification, and the coding and categorisation process to identify research themes. The results of the study show that learning planning in pasraman tends to be flexible and simple, even in some cases without formal learning administration. This condition requires students to rely on pedagogical intuition to adjust the material, methods, and learning difficulty to the diverse student population. In learning practice, acarya utilises various methods, such as lectures, dharmatula discussions, peer tutors, the Dharma Gita, hands-on practice, and educational games. These findings show that the success of multigrade learning in pasraman is greatly influenced by acarya professionals’ ability to improvise in managing learning dynamics.